Correction: Non-faradaic impedance characterization of an evaporating droplet for microfluidic and biosensing applications1. Issue 3 (7th February 2015) - Dak, Piyush; Ebrahimi, Aida; Alam, Muhammad A.
<x xml:space="preserve">Abstract</x> Correction for 'Non-faradaic impedance characterization of an evaporating droplet for microfluidic and biosensing applications' by Piyush Dak et al., Lab Chip, 2014, 14, 2469–2479.